The ecocentrists: a history of radical environmentalism - Woodhouse, Keith Mako (Columbia University Press, 2018)
"Keith Woodhouse explores the political and intellectual history of the radical environmental movement--a movement founded by activists who grew disenchanted with the strategies of the mainstream environmental movement. While mainstream environmentalists (Sierra Club, the Wilderness Society, etc.) emphasized lobbying and working within the political system, groups like Earth First! increasingly championed a more radical approach both tactically and philosophically. Tactically, they embraced direct action--physically blocking or even sabotaging and destroying encroaching industry and infrastructure. Philosophically, they championed views that privileged nature or wilderness over humanity broadly conceived, with little or no regard for the oppressed or impoverished. Such views increasingly set them at odds with other radical movements--feminism, anarchism, etc.--as well as with mainstream environmentalists, all appalled by their simplistic view of complex social problems. Taken together, Woodhouse offers a sophisticated and nuanced picture of modern American environmentalism, showing how it interacted with and was changed by other intellectual, political and social developments over the last half of the twentieth century"--